ANALISIS KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI BANGUN RUANG SISI LENGKUNG KELAS IX DI MTS AL-HUSAINI KARANGASEM - Dewi Maliyani (Universitas Nahdlatul Ulama Pasuruan, 2023)
The purpose of this study is to describe the ability to solve problems with the discovery learning learning model on the material of building the curved side room of class IX at MTs Al-Husaini Karangasem. This type of research is qualitative with a descriptive approach. The main instrument in this study is the researcher himself, and the supporting instruments include observation of teacher activities, problem-solving ability test questions, and interview guidelines. The subjects in this study were class IX students of MTS Al-Husaini Karangasem consisting of 15 students. First, as many as 15 students were given a problem-solving ability test, then the researcher corrected the results of the problem-solving test according to polya indicators to be grouped according to the categories that the researcher had chosen, namely students who had very high, high, medium, low, very low solving abilities. Keywords: Problem Solving Ability, Discovery Learning Learning Model, Build Curved Side Space.